PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ADOBE FLASH UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN AKUNTANSI DI SMK - Wulandari, Lintang; ., Sudiyanto; ., Sohidin (FKIP Universitas Sebelas Maret, 2017)
ABSTRACTThe objectives of this research are to investigate (1) the feasibility of Adobe Flash-based learning media in accounting learning at State Vocational High School, and (2) the effectiveness of Adobe Flash-based learning media to improve the students learning motivation in accounting at State Vocational High School. This research used the research and development (R&D) method. The validation of the product design was done by a learning media expert, a learning material expert, and a practitioner. The subjects of the product testing included 10 students at the preliminary product testing, 30 students in Grade XI Accounting 2 (experimental class) and 30 students in Grade XI Accounting 1(control class) of Sejati Vo-cational High School at the main extended-field testing. The data of research were collected through a questionnaire and documentation. The data were analyzed by using the descriptive analysis and the infer-ential analysis. The results of the research are as follows. Firstly, the developed Adobe Flash-based learn-ing media is feasible to be used in Accounting learning at State Vocational High School. Itâs proven of me-dia feasibility assessment average by a learning media expert which received score of 4.833, and was cat-egorized âvery feasibleâ, assessment of learning material expert which received score of 3.74, and was categorized âfeasibleâ, assessment of practitioner which received score of 4.19, and was categorized âfeasibleâ, and assessment of students which received score of 4.324, and was categorized âvery feasi-bleâ. Secondly, the developed Adobe Flash-based learning media in Accounting is effective to improve the students learning motivation at State Vocational High School. The research shown the difference of learn-ing motivation between the experimental class and the class control with the significance value of 0.000 which was smaller than 0.05, the average scores of learning motivation of experimental class is 4.05 and the control class is 3.61 belong to âhigh